THE CONCEPT OF MANAGEMENT ACTIVITY AND ITS MAIN COMPONENTS - Berdimuratov Adkham Khayrulla uglu (Web of Journals Publishing, 2025)
This article analyzes the main components of managerial activity and their importance in achieving the strategic goals of the organization. Managerial activity is the process of effective management of the organization, achievement of goals and optimization of work processes. To achieve the goals and success of the organization, managers implement the main components such as planning, organizing, directing, controlling and motivating. These components are interconnected in each organization, and efficiency can be achieved through effective cooperation and coordination of work activities of team members. Concrete examples of the implementation of each component and their working mechanisms are considered in the work. Based on the data and analysis, it is shown that each component of the managerial activity is an important process aimed at achieving the overall efficiency of the organization and its strategic goals.
Keywords: Management activity, strategic goals, components, planning, organizing, directing, controlling, motivation, efficiency, team, communication, production, resources, innovation, results, control, effective management.